Preliminary survey and inventory of Calliphoridae and Sarcophagidae (Diptera) in the province of Corrientes, Argentina, with new records of species with forensic importance - Dufek, Matias Ignacio (2015)
This is the first study dealing with the diversity and distribution of Calliphoridae and Sarcophagidae (Diptera) inhabiting the province of Corrientes, Argentina. The work was based on samplings at different locations within the Iberá Marshes and Mburucuyá National Park, bibliographic records, and the examination of materials deposited in several entomological collections. Seventeen species of Calliphoridae and 27 of Sarcophagidae were listed. Twenty five species are recorded for the first time from Corrientes. Four species, Argoravinia brasiliana (Lopes, 1988), Chrysomya putoria (Wiedemann, 1830), Oxyvinia excisa (Lopes, 1950) and Peckia (Euboettcheria) pascoensis (Lopes, 1990), are cited for the first time in Argentina. A list of species recorded with forensic importance is also presented.